Application of New Molecular Genetic Strategies for Transborder Transmission Analysis of Tuberculosis in Irkutsk Region - S. N. Zhdanova; O. B. Ogarkov; E. D. Savilov; I. G. Kondratov (Эпидемиология и вакцинопрофилактика, 2022)
Relevance. The Irkutsk region belongs to the territories of Russia unfavorable for tuberculosis. The situation in the region is exacerbated by the existence of active tourism and trade and transport contacts with Mongolia, which is a country with a higher burden of TB.Aims. To assess the applicability of using subtype-specific PCR tests on clinical samples of TB patients to crossborder transmission analysis of the M. tuberculosis. Materials and methods. we investigated the cohort of 161 sputum and surgical specimens from newly diagnosed TB patients with a positive molecular genetic test (GeneXpert). The epidemic subtypes of the Beijing genotype (subtypes B0/W148, Central Asian, Asian-African 2) were identified by the method PCR with real-time detection (RT-PCR) with primers and probes of our own design. Results. The use of respiratory and surgical specimens with positive results of a molecular genetic test and microscopy makes it possible to differentiate epidemic subtypes of the Beijing genotype in 92.9% of cases. The frequency of detection of the Russian epidemic subtypes Central Asian (45.1%) and B0/W148 (20.3%) in clinical samples does not differ from data strains from the Irkutsk region. The «Mongolian» subtype Asian-African 2 of the Beijing genotype was not identified in the clinical samples in any case. Conclusions. The results indicate the applicability of the used tests for rapid monitoring as a stage in the complex of transboundary surveillance of tuberculosis.